Responses of ticks to immersion in hot bathing water: Effect of surface type, water temperature, and soap on tick motor control. - David J Schimpf; Matthew M Ewert; Victor K Lai; Benjamin L Clarke (PLoS ONE)
Preventing bites from undetected ticks through bathing practices would benefit public health, but the effects of these practices have been researched minimally. We immersed nymphal and adult hard ticks of species common in the eastern United States in tap water, using temperatures and durations that are realistic for human hot bathing. The effect of (a) different skin-equivalent surfaces (silicone and pig skin), and (b) water temperature was tested on Amblyomma americanum, Dermacentor variabilis and Ixodes scapularis nymphs. Overall, the type of surface had a much larger effect on the nymphs' tendency to stay in contact with the surface than water temperature did. Most nymphs that separated from the surface did so within the first 10 s of immersion, with the majority losing contact due to the formation of an air bubble between their ventral side and the test surface. In addition, adult Ixodes scapularis were tested for the effect of immersion time, temperature, and soap on tick responsiveness. Some individual adults moved abnormally or stopped moving as a result of longer or hotter immersion, but soap had little effect on responsiveness. Taken together, our results suggest that the surface plays a role in ticks' tendency to stay in contact; the use of different bath additives warrants further research. While water temperature did not have a significant short-term effect on tick separation, ticks that have not attached by their mouth parts may be rendered unresponsive and eventually lose contact with a person's skin in a hot bath. It should be noted that our research did not consider potential temperature effects on the pathogens themselves, as previous research suggests that some tickborne pathogens may become less hazardous even if the tick harboring them survives hot-water exposures and later bites the bather after remaining undetected.